Korean Constitutionalism and the Special Act to Prosecute Former Presidents Chun Doo-Hwan and Roh Tae-Woo - Waters, David M. (Columbia Journal of Asian Law, 1996)
The Republic of Korea has undergone extensive political change over the past few years. After decades of military and quasi-military dictatorships, in December 1992 Korea elected a civilian president, former dissident leader Kim Young-sam. Although a milestone at the time, representing a break from the authoritarian past, events since then have in many ways transcended Kim’s election. The disclosure in October 1995 that former president Roh Tae-woo had amassed a slush fund of over 650 million while in office, and later allegations that Chun Doo-hwan, who served as president prior to Roh, had coerced 900 million from Korea’s chaebols, sent shockwaves throughout the nation. But in all probability the most stunning development was the decision of President Kim, in late November 1995, to direct his ruling party to enact a law to prosecute Chun and Roh for their respective roles in a 1979 coup d’etat and 1980 bloody crackdown on Korean citizens in Kwangju. This law, enacted in December 1995, and dubbed the ‘Special Act Concerning the May 18th Democratization Movement’ (“Special Act”), has been the subject of criticism for its seeming disregard of significant constitutional issues.’ The Special Act was enacted to seek retribution for the past acts of bloodshed and military usurpation, and to give closure to an unfortunate chapter in the recent history of Korea. However, because the law enables prosecution of a past act for which the statute of limitations has run, it raises issues about its retroactivity, and whether it is a violation of the Korean Constitution’s prohibition against ex post facto laws. Other objections have been raised concerning whether the law encroaches on Korean principles of legality and equality before the law, also issues of a constitutional nature. It has also been protested that Chun and Roh were subjected to double jeopardy as a result of the law’s enactment. Although these challenges to the Special Act are formidable, one cannot feel much sympathy for the former presidents, whose acts showed total disregard for the Constitution which they now seek to hide behind. Still, important negative consequences may result from the current circumventing of constitutional law. Significant strides have been made in Korea towards the foundation for the rule of law. This foundation is still weak, and it is important that corners not be cut.